The Effect of an Anesthetic Support of Endoscopic Gastric Resection on Intraoperative Hemodynamics in Patients with Morbid Obesity - M. I. Neymark; R. V. Kiselev (Общая реаниматология, 2017)
The purpose of the study is to examine the effect of anesthesia and respiratory support parameters on central and peripheral hemodynamics in patients with morbid obesity undergoing an endoscopic gastric resection.Materials and methods. A randomized study of 43 patients with a body weight index of >40 kg/m2 who underwent an endoscopic longitudinal gastric resection (sleeve gastrectomy) was performed. Patients were divided into two groups. In Group 1 (n=22), combined anesthesia based on the low%flow desflurane inhalation was applied along with the mechanical ventilation in the VC%CMV mode with a constant PEEP level. In Group 2 (n=21), combined anesthesia based on the low-flow desflurane inhalation was applied along with the prolonged epidural analgesia (PEA) with 0.2% ropivacaine solution and VC%CMV respiratory pattern, with PEEP dose escalation using titration, inverted respiratory cycle, and a gradual increase in the respiratory rate. The intraoperative monitoring included central and peripheral hemodynamics, blood gases, and ABB.Results. The study demonstrated that there was more stable central and peripheral hemodynamics in Group 2 during the intraoperative period as compared to Group 1, where increased systolic BP, median NMBP, diastolic BP, HR, CI, SVI, and SVRI levels were registered. In addition, in Group 2, РаO2 levels were significantly higherand РCO2 levels were lower during pneumoperitoneum; no significant changes in ABB were recorded.Conclusion. Thoracic epidural analgesia with pneumoperitoneum, increased intraabdominal pressure, and PEEP escalation mode provide stable intraoperative central and peripheral hemodynamics during endoscopic gastric resection in patients with morbid obesity.